Enhanced surface plasmon resonance detection of ascorbic acid using carbon quantum dots thin film - Mohd Daniyal, Wan Mohd Ebtisyam Mustaqim; Fen, Yap Wing; Kariming, Muhamad Zamri; Muhamad Fauzi, Nurul Illya; Hashim, Hazwani Suhaila; Anuar, Muhammad Fahmi; Nugroho, Ferry Anggoro Ardy; Hidayat, Nurul; Abdullah, Huda; Taufiq, Ahmad; Eddin, Faten Bashar Kamal (Springer, 2025)
This research investigates the structural and optical properties of carbon quantum dots (CQDs) for the sensitive detection of ascorbic acid (AA), an essential biomolecule used widely in health and industry. Accurate AA detection is critical for pharmaceutical and food safety applications, and this study demonstrates the use of a prism-based surface plasmon resonance (SPR) sensor with a CQD thin film for label-free and real-time monitoring. CQDs were deposited onto a gold (Au) thin film, and their structural properties were characterized through Fourier transform infrared spectroscopy (FTIR) and atomic force microscopy (AFM). FTIR analysis confirmed the presence of C–H, C≡C, C–N, and C–O bonds on the Au/CQDs surface, while AFM characterization revealed that the CQDs formed a uniformly dispersed, spiky surface evenly distributed across the gold layer. The optical properties of the Au/CQDs thin film were studied using ultraviolet–visible (UV–Vis) spectroscopy, showing an absorption peak of approximately 4.44 a.u. in the range of 260–270 nm, with an optical bandgap of 4.072 eV. When integrated into the SPR sensor, the Au/CQDs thin film demonstrated high sensitivity for AA detection, achieving a detection limit as low as 0.001 µM. Further characterization was conducted to explore the interaction between the Au/CQD thin film and AA, highlighting the film’s potential for use in sensitive biochemical sensing applications.